Street Graffiti and Residents’ Attitude: Izmir City - Umdu, Duygu Cinar (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2017)
Humanity has always been in a struggle to express itself to others. They conveyed through marks and symbols on cave walls, head stones, clay tablets and papyrus before the invention of writing and society. Today urban areas and especially streets are places that carry social marks first-hand. They retain these semiotic signs and become a collective of symbols that link the past to the present and future. Graffiti, which is a part of such communication, is the way people express emotions and ideas to society through symbols. In this study, the attitude of the residents in Izmir City about graffiti, whether they see it as an art form or visual pollution, is studied. A survey was applied to 100 citizens, including fieldwork, photo-shoots and interviews done with 20 people. Part of the graffiti in Izmir urban identity is determined and the results are presented. Keywords: Graffiti, resident’s attitude, Izmir.
Keywords: 11. Sustainability